2007
DOI: 10.2139/ssrn.1343667
|View full text |Cite
|
Sign up to set email alerts
|

M&A and Post Merger Integration in Banking Industry: The Missing Link of Corporate Culture

Abstract: The intense concentration process taking place in the financial systems of the major countries has attracted substantial attention from stakeholders and academics. The impact of M&A on value creation and efficiency / effectiveness improvements of banks involved appears, on the whole, disappointing and still hard to create benefits for customers. The reason seems to lie in the difficulty of governing a post-merger integration process, which generally requires good governance and management practices, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Buono et al (1985) suggested that even within the same industry, merging two different, though viable, organizational cultures present major difficulties. More recently, Carretta et al (2007) found that cultural clashes can generate conflicts and adverse effects on the timing and effectiveness of post-merger integration. Therefore, organizational effort to integrate diverse groups struggle with the organizational differences of merger partners.…”
Section: Research Objectives and Hypothesesmentioning
confidence: 99%
“…Buono et al (1985) suggested that even within the same industry, merging two different, though viable, organizational cultures present major difficulties. More recently, Carretta et al (2007) found that cultural clashes can generate conflicts and adverse effects on the timing and effectiveness of post-merger integration. Therefore, organizational effort to integrate diverse groups struggle with the organizational differences of merger partners.…”
Section: Research Objectives and Hypothesesmentioning
confidence: 99%